Notice of a Casket of Amenhotep II. (XVIII. Dynasty c. 1430 B.C.) in the late Mr A H Rhind’s Egyptian Collection, now in the Scottish National Museum of Antiquities - Petrie, W M Flinders (Proceedings of the Society of Antiquaries of Scotland, 1896)